La santé mentale des francophones en situation minoritaire au Canada : un portrait tiré de l’Enquête sur la santé dans les collectivités canadiennes-Santé mentale 2012 - Bouchard, Louise; Colman, Ian; Dubois, Alejandra; Sucha, Ewa (Université d’Ottawa et Institut du Savoir Montfort, 2019)

The mental health of Francophone minorities: An overview from the Canadian community health survey-Mental health 2012 - Bouchard, Louise; Colman, Ian; Dubois, Alejandra; Sucha, Ewa (University of Ottawa & Institut du Savoir Montfort, 2019)

La santé mentale des francophones et des anglophones vivant en situation minoritaire au Canada [infographie] - Bouchard, Louise; Dubois, Alejandra; Sucha, Ewa (2019)

Mental health status of Francophones and Anglophones living in minority situations in Canada [infographic] - Bouchard, Louise; Dubois, Alejandra; Sucha, Ewa (2019)

Profil santé mentale des communautés francophones en situation minoritaire au Canada. Rapport abrégé - Bouchard, Louise; Dubois, Alejandra; Sucha, Ewa; Colman, Ian (Université d'Ottawa et Institut du Savoir Montfort, 2019)

Vivre et travailler en français à Iqaluit (Nunavut) : regards de professionnels de la santé sur le capital social de la communauté francophone - Charrier, Marie-Josée (Revue du Nouvel-Ontario, 2019)

Implantation d’un programme de formation à l’offre active de services en français auprès des futurs professionnels de la santé et des services sociaux dans une université canadienne - Dubouloz-Wilner, Claire-Jehanne; Benoît, Josée; Savard, Jacinthe (Éducation francophone en milieu minoritaire, 2019)

Modèle de mobilisation communautaire pour l’amélioration de la santé et de la vitalité des communautés d’expression anglaise au Québec - Kueber, Russell; Richardson, Mary (Réseau communautaire de santé et des services sociaux et Institut national de santé publique du Québec, 2019)

À l’intersection des définitions de langues : portrait des communautés linguistiques au Québec et dans les réseaux territoriaux de services en 2016. La langue, déterminant de l'état de santé et de la qualité des services - Lussier, Marie-Hélène; Tu, Mai Thanh; Blaser, Christine (Institut national de santé publique du Québec, 2019)

At the intersection of language definitions: A portrait of linguistic communities in Québec and its territorial service networks in 2016. Language as determinant of health and quality of services - Lussier, Marie-Hélène; Tu, Mai Thanh; Blaser, Christine (Institut national de santé publique du Québec, 2019)

The linguistic continuity of Ontario's minority Francophone population: Examining the relationship between culture and linguistic practices - Nault, Jean-François (Canadian Review of Sociology, 2019)
Despite decades of policy aimed at the maintenance of Francophone communities in Ontario, the proportion of individuals with French as a mother tongue or who speak French most often at home has steadily declined. Research on language retention has highlighted the importance of sociodemographic and structural factors in understanding minority language practices. However, given the relationship between culture and action, this paper examines how cultural factors contribute to Franco-Ontarians’ linguistic practices. Results indicate that beyond couple composition and the concentration of minority-language speakers, cultural factors including identity, cultural consumption, and values play an instrumental role in Franco-Ontarians’ linguistic continuity. The importance of considering linguistic continuity as part of a “package” of cultural practices is discussed.

Étude de besoins sur les services de santé mentale en français. Rapport final - PGF Consultants (Société Santé en français et Santé Canada, 2019)

Des soins de santé et des services sociaux sécuritaires dans sa langue. Réponse au projet de Cadre canadien sur la qualité des soins et la sécurité des patients - Société Santé en français (2019)